Soy beta-Conglycinin (7S Globulin) Reduces Plasma and Liver Cholesterol in Rats Fed Hypercholesterolemic Diet - Ferreira, Ederlan de Souza [UNESP]; Silva, Maraiza Aparecida [UNESP]; Demonte, Aureluce [UNESP]; Neves, Valdir Augusto [UNESP] (Mary Ann Liebert, Inc., 2011)
The aim of this study was to examine the comparative hypocholesterolemic effect of soybean 7S fraction in rats fed a high-cholesterol diet. Soybean 7S globulin (beta-conglycinin) was administered orally once a day to rats, and the effects were measured after 28 days. Wistar rats were divided into four groups: standard diet (STD) (casein alone), hypercholesterolemic (HC) diet (STD plus 1 g/100 g cholesterol and 0.5 g/100 g cholic acid), HC+7S(1) diet (HC diet plus 200 mg of 7S/kg of body weight/day), and HC+7S(2) diet (HC diet plus 300 mg of 7S/kg of body weight/day). Food intake, weight gain, animals' growth, and feeding efficiency ratio were similar among the STD and three HC groups, indicating that these parameters were not affected by treatments. Animals that had received different doses of soybean 7S globulin had lower total cholesterol (TC), triglycerides (TG), and low-density lipoprotein (LDL)/high-density lipoprotein (HDL) ratio in serum and lower levels of hepatic TC and TG than those fed only the HC diet. The atherogenic indexes of HC+7S(1) and HC+7S(2) groups were 40% and 55% lower than that of the HC group, respectively. The results showed that the oral daily administration of beta-conglycinin in the diet to HC rats, at between 1.85% and 2.75% of total ingested protein, promotes the reduction of TC, LDL-cholesterol, and TG and an increase in HDL-cholesterol in the plasma, besides a small but significant reduction in cholesterol and TG levels in the liver of the animals as well as a reduced atherogenic index.
Keywords: cholesterol; beta-conglycinin; hypercholesterolemic diet; rats; triglycerides